A Review of Hypermobile Ehlers-Danlos Syndrome - Prasad, P. Dharani (Asian Journal of Pharmaceutics (AJP), 2023)
Ehlers-Danlos syndrome (EDS) is a rare connective tissue disorder that affects the collagen metabolism in which collagen deficiency occurs. According to the 2017 international classification of the EDS, 13 different subtypes are caused by pathogenic variants in 19 different genes that encode collagen and collagen-modifying proteins. Among the 13 subtypes of EDS, hypermobile EDS (hEDS) is the most common one. hEDS is formerly known as type III EDS. The cause of hEDS is idiosyncratic. Inheritance is autosomal dominant. The patients of hEDS have softness, stretchiness, fragility, bruisability, and poor wound healing when compared to normal patient. Hernias may also be more common in persons with hEDS who undergo abdominal surgery, such as laparotomy or C-section. Symptoms of hEDS include soft and elastic or stretchy skin, easy bruises, and persistent musculoskeletal pain. Three disease phases were proposed in a 2010 study: A “hypermobility” phase, a “pain” phase, and a “stiffness” phase. The prevalence rate of hEDS is 80–90% of all the cases of EDS. The cause of hEDS, which has a genetic inheritance pattern similar to Alzheimer’s disease, is not known to be a gene mutation. The treatment of hEDS depends on signs and symptoms present in each patient, and treatment differs from patient to patient. There is no particular treatment for hEDS, and physical therapy is often recommended to strengthen muscles and improve joint stability. Pain medication such as physiotherapy, occupational therapy, orthopedic instruments, aquatic therapy, and cognitive behavioral therapy.